PENGARUH GREEN MARKETING TERHADAP MINAT DAN KEPUTUSAN PEMBELIAN KONSUMEN PT. SINAR SOSRO TABANAN - I GUSTI LANANG GOLDEN JAYADI; WAYAN ARDANI (GANEC SWARA, 2024)
Ecological problems due to the increasing volume of plastic waste are a global concern, with several Asian countries including Indonesia as the main contributor of plastic waste to the oceans. PT Sinar Sosro hopes that by implementing green marketing it can influence customer purchasing decisions which include customer confidence and confidence in the products purchased. This study aims to evaluate the impact of green marketing on consumer choice and purchase intention at PT Sinar Sosro Tabanan Branch Office. The type of research used is quantitative research. The research subjects were all consumers of PT Sinar Sosro Tabanan Head Office with samples taken using accidental sampling technique totaling 60 samples. Partial Least Square (PLS) was used as a data processing tool. The results found that environmentally friendly marketing has a positive and significant effect on purchase intention with a coefficient of 0.788, and a purchase decision coefficient of 0.646. Purchase intention is also shown to mediate the impact of green marketing on purchasing decisions with a partial effect. Good implementation of green marketing increases consumer purchasing decisions and purchase interest, and supports PT Sinar Sosro in maintaining market share in the midst of intense beverage industry competition.